IDENTIFICATION OF SAFE DISTANCE AGAINST DISPOSAL SLOPE: IDENTIFIKASI JARAK AMAN TERHADAP LERENG DISPOSAL - Abdul Jalil; Risal Gunawan; Eko Wicaksono; Waterman Sulisyana Bargawa (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2023)
Initial mining activities need to remove overburden so it is necessary to find a safe and efficient location to avoid areas that still contain economical excavated materials. This disposal or stockpiling must be arranged considerably to meet the geotechnical design requirements. Other factors, influenced by economics and safety are very important in planning the disposal site. The purpose of this study is to determine the safe distance to disposal for PE pits based on laboratory tests. The study showed that the optimal disposal values for PE pits were 14˚ for a slope height of 50 m, 13˚ for a slope height of 80 m, and 12˚ for a slope height of 100. The Stability of the slope will be better by reducing the slope angle of the disposal slope. The analysis shows that the safe distance to disposal for PE pits is 45 m slope height with 50 m safety distance, 50 m slope height with 69 m safety distance, and 76 m slope height with 100 m safety distance. The higher the disposal slope, the smaller the slopes formed, and the greater the safety distance if the slope height increases.